Rezension von: Badal, Richard A., Fliegerhorst Crailsheim - Stihler, Daniel (Württembergisch Franken, 2000)
Richard A. Badal, Fliegerhorst Crailsheim, Crailsheim (Verlag Robert Baier) 1997. 94 S., zahlt. Abb. u. 1 Kartenbeilage.